(untitled) (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2024)
Literature is a noble work that needs to be preserved for the continuity of the values taught to future generations. Preservation can be done by understanding and studying the values contained in literature itself. The Dayak gawai mantra is a mantra full of noble values for generations and important lessons for life. The aim of this research is to describe the values contained in the Mantra for the Dayak gawai ceremony of the Kantuk tribe which is carried out every year, in addition to describing what equipment is used in this tradition. The method used is a descriptive qualitative method with an ethnographic approach. The method also uses triangulation techniques to verify data. Data collection was carried out by interviews, documentation and distribution of questionnaires. The research results show that the value of the Gawai Dayak Mantra is related to divinity and respect for nature as well as the values of unity and equality. The equipment used includes sesjen (traditional food and drinks) and kitchen utensils and farming equipment.